The Professional Guest: conceptualizing home visits in palliative care settings - Ron Sabar; Inbal Halevi Hochwald; Moran Weiss; Gila Yakov (Palliative Care and Social Practice, 2024)
Background: Home-based palliative care is a growing trend, necessitating a deeper understanding of the unique challenges faced by professional staff members in this setting. The shift to home-based care has been driven by advances in technology, changing demographics, and a move toward more patient-centered approaches. As a care setting, the home environment offers distinct characteristics, presenting both advantages and drawbacks for patients and healthcare providers. Objectives: This study aims to explore the experiences and perceptions of professional staff members providing palliative care in patients’ homes. Design: A qualitative descriptive study. Methods: Qualitative study with 36 home-based hospice professionals using questionnaires and interviews. Thematic analysis identified key themes in staff experiences and challenges. Results: The central theme of “The Professional Guest” highlights the hybrid identity and boundary role professional staff members must navigate, being both medical professionals and guests in the patient’s domain. Four sub-themes emerged: (1) Observing and Applying, emphasizing the conscious scanning of the home environment to build trust and tailor care plans; (2) Asking for Permission, respecting the patient’s territory and adapting to their norms; (3) Expecting the Unexpected, maintaining flexibility and improvising in unfamiliar situations; and (4) Preparing the Ground for Your Absence, equipping patients and families with comprehensive self-care guidance during professional staff members’ absences. Conclusion: The “Professional Guest” phenomenon captures the complexities of providing care in patient’s homes, necessitating a delicate balance between professionalism and personal vulnerability. Specialized training programs and policies should be developed to support professional staff members in navigating this hybrid identity and effectively negotiating the boundaries between professional and personal spheres.